Exploration of Tetrahydroisoquinoline- and Benzo[c]azepine-Based Sphingosine 1-Phosphate Receptor 1 Agonists for the Treatment of Multiple Sclerosis - Cha, Eunji; Kim, Jushin; Gotina, Lizaveta; Kim, Jaehwan; Kim, Hyeon Jeong; Seo, Seon Hee; Park, Jeong-Eun; Joo, Jeongmin; Kang, Minsik; Lee, Jaeick; Hwang, Hayoung; Kim, Hak Joong; et al. (American Chemical Society, 2023)
Because of the wide use of Fingolimod for the treatmentof multiplesclerosis (MS) and its cardiovascular side effects such as bradycardia,second-generation sphingosine 1-phosphate receptor 1 (S1P1) agonistdrugs for MS have been developed and approved by FDA. The issue ofbradycardia is still present with the new drugs, however, which necessitatesfurther exploration of S1P1 agonists with improved safety profilesfor next-generation MS drugs. Herein, we report a tetrahydroisoquinolineor a benzo[c]azepine core-based S1P1 agonists suchas 32 and 60 after systematic examinationof hydrophilic groups and cores. We investigated the binding modesof our representative compounds and their molecular interactions withS1P1 employing recent S1P1 cryo-EM structures. Also, favorable ADMEproperties of our compounds were shown. Furthermore, in vivo efficacyof our compounds was clearly demonstrated with PLC and EAE studies.Also, the preliminary in vitro cardiovascular safety of our compoundwas verified with human iPSC-derived cardiomyocytes.